EU:N rahoituskehykset - Suomen asema seuraavalla kehyskaudella 2014-2020 - Markku Kotilainen; Sixten Korkman; Jyrki Niemi; Nuutti Nikula; Hannu Kaseva; Lauri Kettunen (The Research Institute of the Finnish Economy (ETLA), 2009)
The study analyses the financial framework of the European Union in 2014-2020 and the prospects of Finland in this framework. The study is structured according to budget headlines the most central of which are the natural resources (agriculture and rural development), cohesion (regional and structural policies), and competitiveness. Scenarios concerning the future are built upon alternative developments in the composition of the budget. The development of Finland's net payment position is analysed using different assumptions of GDP growth. A central assumption in most scenarios is the fact that the budget shares of the natural resources and regional and structural policies will decline substantially, also giving room to cut the size of the budget. According to our study, Finland will be able to adjust to the changes in the structure of the budget. In the case of agriculture, an increase in the size of farms, productivity growth, and especially the assumed continued national agricultural support will have an outcome that the level of agricultural output does not change substantially. In regional policy, a decrease in the growth of or cuts in EU regional subsidies can be compensated for by national subsidies. The pressures for adjustment which Finland will face during the future financial framework will be decreased because during the current financial period Finland already experienced many adjustments. Finland will be able to respond to the growth of funding under the competitiveness headline, if the country will be able to develop capabilities to apply for research and other competitiveness funding.
Keywords: O52; F53; F55; H87; Q18; R58; I28; 330; European Union; Finland; EU budget; agricultural policy; regional policy; competitiveness; research and development (R&D); EU-Finanzen; EU-Staaten; Finnland